ATP requirement of the sodium-dependent magnesium extrusion from human red blood cells. - Frenkel, E J (1989)
1. Competitive behaviour detectable in the stimulatory action of external sodium (Nao+) and internal magnesium (Mgi2+) corroborates the idea that Nao+-dependent Mg2+ extrusion is a Mgi2+-Nao+ exchange. 2. Mg2+-loaded resealed cells made from metabolically starved cells (with less than 5 mumols/l cells of ATP), show hardly any Nao+-dependent Mg2+ outflow. Incorporation of ATP during lysis-resealing restores this Mg2+ transport. Half-saturation for the effect is reached at an initial ATP concentration of about 150 mumols/l cells. 3. Adenylyl(beta, gamma-methylene) diphosphonate (AMP-PCP) and AMP had no restituting effect, indicating that in order to act ATP must be hydrolysed. 4. Nao+-dependent Mg2+ outflow is not inhibited by vanadate concentrations that completely block the Ca2+ or Na+ pump. Therefore, the Nao+-Mgi2+ exchange does not fall into the class of cation pumps of the E1E2 type. 5. Yet the fact that reversal of the Na+ gradient fails to reverse the direction of the Na+-dependent Mg2+ transport in human red cells (Lüdi & Schatzmann, 1987) and that at equal Na+ concentration inside and outside the rate of Mg2+ transport is still 50% of that at a Na+ concentration difference of approximately 100 mM across the membrane suggests that the Na+ gradient, or the cation gradients in general, are not the only driving forces for Mg2+ movement. The assumption that there is energy input from ATP hydrolysis is compatible with these observations, whereas proposing the action of a protein kinase fails to explain them. 6. It is concluded that the Nao+-Mgi2+ exchange system has an absolute requirement for ATP and that it is more probable that ATP is supplying energy for transport rather than activating transport by protein phosphorylation or simply by binding.